Social Media as an Effective Tool for Integrated Marketing Communications: Evidence from China - LIN, XINYI (2018)
Abstract The deep penetration of social media has brought a significant influence on people’s lives and marketing communications. Social media has been realised as an effective tool in marketing as it allows interactive and two-way communication between consumers and organisations. An increasing number of companies around the world has incorporated social media in their businesses. The purpose of this research is to find out whether social media could be used as an effective tool in companies’ Integrated Marketing Communications programmes in China through examining the impact of social media on consumers’ purchasing decisions from three dimensions: attitude, e-WOM (electronic word-of-mouth) as well as consumer behaviour. A questionnaire approach was employed in this research. Data was collected from 157 Chinese consumers and analysed through SPSS 24. All data was analysed through using descriptive statistics, correlation analysis, multiple linear regression analysis and One-Way ANOVA. The results indicated social media is able to influence the consumers purchasing decisions and all three factors (attitude, e-WOM and consumer behaviour) has had impacts on consumers’ purchasing decisions. However, compared to e-WOM and consumer behaviour, consumers’ attitude has a relatively insignificant influence on consumers purchasing decisions. Based on the findings, some managerial implications are provided at the end of the research.